2012
DOI: 10.2147/cpaa.s25784
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 clinical study of the acute and subacute safety and proof-of-concept efficacy of carbohydrate-derived fulvic acid

Abstract: BackgroundThe purpose of this research was to determine the acute and subacute safety and proof-of-concept efficacy of carbohydrate-derived fulvic acid (CHD-FA).MethodsIn this double-blind study, 30 male volunteers with predetermined atopy were randomly assigned to either Group A or Group B, each consisting of 15 participants. In part 1 of the study, the groups were administered increasing amounts of CHD-FA, ranging from 5 mL to 40 mL, provided that no adverse events had occurred at the previous dosage. In par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…Interestingly, oral administration of FA ≥100 mg/kg effectively reduced carrageenan-induced paw edema in rats [ 32 ]. In another study, carbohydrate-derived FA showed potent activity against fungal pathogens with lower minimum inhibitory concentration (MIC) values (equal or less than 5 mg/mL), while the cytokine interleukin 6 mediated-inflammation response was significantly inhibited [ 14 ]. In the human clinical toxicity assessment study, FA is indicated to be safe in humans at a daily dosage of 1.8 g (equal to purified FA at 30 mg/BW/day) [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, oral administration of FA ≥100 mg/kg effectively reduced carrageenan-induced paw edema in rats [ 32 ]. In another study, carbohydrate-derived FA showed potent activity against fungal pathogens with lower minimum inhibitory concentration (MIC) values (equal or less than 5 mg/mL), while the cytokine interleukin 6 mediated-inflammation response was significantly inhibited [ 14 ]. In the human clinical toxicity assessment study, FA is indicated to be safe in humans at a daily dosage of 1.8 g (equal to purified FA at 30 mg/BW/day) [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fulvic acid (FA), one fraction of HA, has a lower molecular weight and a higher oxygen content than other HA components [ 3 ]. Several studies showed that FA is a potential safe natural active ingredient of HA [ 14 , 15 ]. As a dietary supplementation, FA can be found in a liquid form as a component of mineral colloids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant decrease in the skin prick test was observed (Table ). It was concluded that this product was safe at these dosages (Gandy et al, ).…”
Section: Clinical Studiesmentioning
confidence: 99%
“…An initial randomized double blind controlled trial indicated that fulvic acid was well-tolerated in patients with eczema, where side effects were minimal and severity and erythema were significantly reduced compared with the placebo control ( Gandy et al, 2011 ). A subsequent phase 1 clinical study carried out to determine the safety profile of CHD-FA, showed that this agent was able to elicit anti-inflammatory properties in addition to being non-toxic when used as an oral formulation ( Gandy et al, 2012 ). This anti-inflammatory activity was also shown in a rat wound model, where the use of a topical cream enhanced wound healing and was non-toxic during both acute and chronic treatments ( Sabi et al, 2012 ).…”
Section: Fulvic Acidmentioning
confidence: 99%